HERITABILITY AND RESPONSE TO SELECTION FOR GROWTH IN THE F1 GENERATION OF CRAYFISH Procambarus acanthophorus - Carlos Perez Rostro (Tropical and Subtropical Agroecosystems, 2012)
The crayfish Procambarus (A.) acanthophorus is a crustacean relevant for regional fisheries in Veracruz, Mexico, with ideal aquaculture characteristics, except for its small size. Thus, a study was conducted with the aim to evaluate the response to selection in the first generation (F1) and heritability (h2) of the crayfish. A group of 2135 organisms with average weight (±S.D.) 4.1 ± 1.79 g were captured from the wild (G0), and 10 % (i = 1,755) of the population was selected with the highest body weight by gender: 140 females (5.62 ± 1.97 g) and 48 males (6.02 ± 1.9 g), forming the progenitors of the selection line (LS). The control line (LC) was formed from a batch obtained at random. Thirty full-sib families were obtained per line (F1), and cultured individually for five months in a recirculation system with mechanical and biological filtration under laboratory conditions and supplied with food twice a day (Camaronina 35 % protein). Monthly heritability (h2) in broad sense was estimated using a full-sib design, based on the components of variance (ANOVA REML method) and the growth was compared between lines in the F1. The mean h2's for weight after five months of culture were 0.27±0.11 for LC and 0.34±0.12 for LS, being the LS in F1 9.6 % heavier than the LC, with 84 and 88 % survival at the end of the study. It is possible to implement a breeding program based on selection for species growth.